2019
DOI: 10.1021/acs.inorgchem.9b01362
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Large Volume Collapse, Plane-to-Chain, Insulator to Metal Transition in CaMn2Bi2

Abstract: In-situ high pressure single crystal X-ray diffraction study reveals that the quantum material CaMn2Bi2 undergoes a unique plane to chain structural transition between 2 and 3 GPa, accompanied by a large volume collapse. CaMn2Bi2 displays a new structure type above 2.3 GPa, with the puckered Mn honeycomb lattice of the trigonal ambient-pressure structure converting to one-dimensional (1D) zigzag chains in the high-pressure monoclinic structure. Single crystal measurements reveal that the pressure-induced struc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 74 publications
7
15
0
Order By: Relevance
“…The zero-pressure bulk modulus of AP- and HP-Mg 3 Sb 2 is 38 and 46 GPa, respectively, while the zero-pressure bulk modulus of AP- and HP-Mg 3 Bi 2 is 37 GPa and 49 GPa, respectively. The HP structures of both compounds are slightly stiffer than the AP structures, similar to the behavior reported for CaMn 2 Bi 2 . The zero-pressure bulk moduli of AP-Mg 3 Sb 2 and AP-Mg 3 Bi 2 obtained in this study are comparable to the results of resonant ultrasound spectroscopy (36 and 38 GPa, respectively) and DFT (42 and 37 GPa, respectively) …”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The zero-pressure bulk modulus of AP- and HP-Mg 3 Sb 2 is 38 and 46 GPa, respectively, while the zero-pressure bulk modulus of AP- and HP-Mg 3 Bi 2 is 37 GPa and 49 GPa, respectively. The HP structures of both compounds are slightly stiffer than the AP structures, similar to the behavior reported for CaMn 2 Bi 2 . The zero-pressure bulk moduli of AP-Mg 3 Sb 2 and AP-Mg 3 Bi 2 obtained in this study are comparable to the results of resonant ultrasound spectroscopy (36 and 38 GPa, respectively) and DFT (42 and 37 GPa, respectively) …”
Section: Resultssupporting
confidence: 85%
“…The HP structures of both compounds are slightly stiffer than the AP structures, similar to the behavior reported for CaMn 2 Bi 2 . 21 The zero-pressure bulk moduli of AP-Mg 3 Sb 2 and AP-Mg 3 Bi 2 obtained in this study are comparable to the results of resonant ultrasound spectroscopy (36 and 38 GPa, respectively) 14 and DFT (42 and 37 GPa, respectively). 37 The question of whether or not Mg 3 Pn 2 (Pn = Sb, Bi) are layered structures has been under debate.…”
Section: ■ Results and Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Recent experimental and theoretical studies find CaMn 2 Bi 2 to host many intriguing properties including large anisotropic magnetoresistance 16 and a planeto-chain structural transition 17 , but most curiously it has been suggested that CaMn 2 Bi 2 may be a hybridizationgap semiconductor. 18,19 In line with this claim, lowtemperature electrical transport measurements find a slight increase of the gap under pressure.…”
Section: Introductionmentioning
confidence: 99%